High burden of infections caused by ESBL-producing MDR Escherichia coli in paediatric patients, Yangon, Myanmar. Issue 1 (14th February 2021) - San, Thida; Moe, Ingyin; Ashley, Elizabeth A; San, Nilar
Abstract: Background: There is mounting evidence of a high burden of antimicrobial-resistant infections in children in low- and middle-income countries (LMICs). Objectives: To detect the frequency of ESBL-producing Escherichia coli in clinical specimens from paediatric patients attending Yangon Children's Hospital in Myanmar. Methods: All children attending Yangon Children's Hospital who had clinical specimens submitted to the hospital diagnostic microbiology laboratory from June 2019 to December 2019 were included in the study. Specimens were processed routinely using standard methods with BD Phoenix used for pathogen identification and susceptibility testing. Presence of ESBLs was determined using the cephalosporin/clavulanate combination disc method with confirmation by PCR. Results: From 3462 specimens submitted to the Microbiology Laboratory, a total of 123 E. coli were isolated. Among them, 100 isolates were phenotypically ESBL producers, 94 (76.4%) of which were confirmed by PCR [82/94 (87%) CTX-M, 72/94 (77%) TEM, 1/94 (1%) SHV]. Most of the ESBL-producing E. coli were isolated from urine samples (52.1%, 49/94) and the majority were from the surgical unit (61.7%, 58/94). Only 34/94 (36%) isolates were susceptible to meropenem. Conclusions: This study confirms a high proportion of infections caused by ESBL-producing and MDR E. coli in children hospitalized in Yangon, where access to effective second-line antimicrobials is limited.